2017
DOI: 10.3762/bjoc.13.105
|View full text |Cite
|
Sign up to set email alerts
|

A concise and practical stereoselective synthesis of ipragliflozin L-proline

Abstract: A concise and practical stereoselective synthesis of ipragliflozin L-proline was presented starting from 2-[(5-iodo-2-fluorophenyl)methyl]-1-benzothiophene and 2,3,4,6-tetra-O-pivaloyl-α-D-glucopyranosyl bromide without catalyst via iodine–lithium–zinc exchange. The overall yield was 52% in three steps and the product purity was excellent. Two key diastereomers were prepared with efficient and direct access to the α-C-arylglucoside.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Currently, in the market, it is available in four different formulations: Jardiance (empagliflozin, 10 mg/25 mg tablets), Glyxambi (empagliflozin and linagliptin, 10/5 mg or 25/5 mg tablets), Synjardy (empagliflozin and metformin, film-coated tablets: 5 mg or 12.5 mg/1000 mg, and 5 mg/850 mg) and Synjardy XR (empagliflozin and metformin extended-release, 12.5 mg/1000 mg tablets). 42 An early discovery patent (WO2006117359, 2006) describing the synthesis of empagliflozin (5) is discussed in Scheme 20. 43 The synthesis involves a total of eight steps with an overall yield of 8% and commences from commercially available 2-chloro-5-bromobenzoic acid (26c), which was treated with oxalyl chloride to generate in situ the acid chloride 26c′.…”
Section: Empagliflozinmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, in the market, it is available in four different formulations: Jardiance (empagliflozin, 10 mg/25 mg tablets), Glyxambi (empagliflozin and linagliptin, 10/5 mg or 25/5 mg tablets), Synjardy (empagliflozin and metformin, film-coated tablets: 5 mg or 12.5 mg/1000 mg, and 5 mg/850 mg) and Synjardy XR (empagliflozin and metformin extended-release, 12.5 mg/1000 mg tablets). 42 An early discovery patent (WO2006117359, 2006) describing the synthesis of empagliflozin (5) is discussed in Scheme 20. 43 The synthesis involves a total of eight steps with an overall yield of 8% and commences from commercially available 2-chloro-5-bromobenzoic acid (26c), which was treated with oxalyl chloride to generate in situ the acid chloride 26c′.…”
Section: Empagliflozinmentioning
confidence: 99%
“…Currently, in the market, it is available in four different formulations: Jardiance (empagliflozin, 10 mg/25 mg tablets), Glyxambi (empagliflozin and linagliptin, 10/5 mg or 25/5 mg tablets), Synjardy (empagliflozin and metformin, film-coated tablets: 5 mg or 12.5 mg/1000 mg, and 5 mg/850 mg) and Synjardy XR (empagliflozin and metformin extended-release, 12.5 mg/1000 mg tablets). 42…”
Section: Synthesis Of Gliflozinsmentioning
confidence: 99%
“…Notably, this methodology afforded the target compound using advanced intermediates such as 15 and 28, which increased the overall yield. Although the report by Ma and Zhou did not offer any information regarding the α/β ratio, a recent work by the same group of authors reported diastereomeric excesses between 85 and 97% . The use of zinc as the catalyst in the stereoselective C-glycosylation reactions was also explored for the synthesis of other gliflozins such as 9 , 2 , and 3 . ,, …”
Section: Synthesis Of Gliflozinsmentioning
confidence: 99%
“…Although the report by Ma and Zhou did not offer any information regarding the α/β ratio, a recent work by the same group of authors reported diastereomeric excesses between 85 and 97%. 87 The use of zinc as the catalyst in the stereoselective C-glycosylation reactions was also explored for the synthesis of other gliflozins such as 9, 2, and 3. 54,57,58 Lemaire et al 54 described a stereoselective arylzinc substitution based on the reports of Gagnéand co-workers 88−90 and Nukada et al 91 The reaction proceeded through a nucleophilic substitution with the formation of an intermediate oxocarbenium via vicinal group participation by the pivaloyl ester at the 2-position (Figure 11).…”
Section: Organic Process Research and Developmentmentioning
confidence: 99%
“…Using these criteria, we produced a list of 43 chiral probes suitable for absolute configuration studies (Table S2). Ipragliflozin was already known to form a cocrystal with L‐proline, [43] so L‐proline was also included in the virtual screen for ipragliflozin.…”
Section: Introductionmentioning
confidence: 99%